Literature Review on Improving Data Security using DES and DCT - Singhal, Vikas; Singh, Devendra; Gupta, Sanjai (International Journal of Computer Sciences and Engineering, 2021)
Steganography is the art and science for hiding information by embedding data into cover media. Image processing in steganography is done mainly by using spatial domain and frequency domain. In this review literature, hiding spatial domain using LSB technique and hiding frequency domain using DCT technique is studied and compared. BMP cover images with 256x256 and 512x512 resolutions for LSB and DCT techniques are used for experimental study. For DCT technique, various BMP image is converted to JPEG image. The DCT technique is used to hide the data into the JPEG cover image. The resultant stego image obtained in JPEG is converted to BMP stego image. Thereafter, the comparison tool PSNR is used to compare the BMP images obtained from LSB and DCT. The data security and privacy play an important role for data transmission for exchanging information over internet. The two techniques like; cryptography and steganography both are pillars to be utilized for securing digital data by using different methods specifically DES (Data Encryption Standard) and DCT (Discrete Cosine Transform). The mixture of DES and DCT improves the digital data security with multiple level of security for encryption process which shows better results. In this research, we analyze the combination of cryptographic method with DES technique and stenographic method with DCT technique to develop a framework for digital data security environment. This paper also presents a proposed least significant bit (LSB) based framework for DES and DCT to secure digital data with better compression approach.